Communication Patterns on Implementation of E-Planning in Rokan Hilir Regency - Muhd Ar. Imam Riauan; Nanang Dwi Cahyono; Aini Maznina A.Manaf (Journal of Applied Engineering and Technological Science (JAETS), 2022)
A communication pattern is a procedure that may describe a stage of communication that takes place inside a particular communication context. This stage of communication can take place everywhere communication takes place. The process of communication may be understood by looking at communication patterns. The pattern of communication that was utilized in the process of putting e-planning into action in the Rokan Hilir district was the subject of this study. The research technique employed in this investigation was a qualitative research method, which involved summarizing the findings of research conducted in the field. There were a total of eight persons included as participants in this study. Five informants from Regional Apparatus Organizations act as Heads of Program Subdivision in Rokan Hilir Regency, in addition to 1 key informant who is the head of BAPPEDA of Rokan Hilir Regency Head of Program Subdivision. According to the findings of this research, Communication Pattern is utilized throughout the e-planning process with a mentorship program at each phase of the procedure. SIPD is utilized throughout the communication procedure to guarantee that each proposal gets entered into the system. The Regional Head, the Regency DPRD, Regional Apparatus Organizations, Community Apparatus Organizations, and the Community all participate in the coordination process. The community functions as a hub for communication and the generation of ideas, which in turn serve as the foundation for development projects that will be carried out in the Rokan Hilir Regency.